The Tulip touch - Fine, Anne. (London : Puffin Books, 2006)
Natalie, who lives in the large hotel managed by her father, has a dangerous friendship with Tulip, the wildly uncontrollable girl on a neighboring farm.
Young Adult.
Young Adult
Keywords: Behavior -- Fiction; Emotional problems -- Fiction; Friendship -- Fiction; Hotels, motels, etc. -- Fiction; Emotional problems -- Fiction; Friendship -- Fiction; Hotels and motels -- Fiction; Human behavior -- Fiction